TEACHING VOCABULARY: INDONESIAN EFL STUDENT TEACHER’S CHALLENGES WRITING ENGLISH DURING COVID-19 PANDEMIC - Ida Fitri Anggarini; Vivi Olivia Rahmah; Zahra Cindy Aditya; Soffi Salma Azzura; Alsya Kurnia Putri; M. Syafi’i Aditya (IAI Al-Qolam, 2023)
English as a Foreign Language (EFL) means learning English in a non-English speaking country such as Indonesia. By learning EFL, EFL educators encourage students to improve their English skills through listening, speaking, reading, and writing. In writing skills, teaching vocabulary has crucial points. Focusing on learning English vocabulary, this research took a case in several schools in East Java. Under a qualitative case study, the researcher addressed two main methods to two Indonesian EFL students in Malang and one Indonesian EFL teacher in Banyuwangi and Tulungagung. By using reflective essays and virtual interviews as the methods, the data concluded that most of the challenges found had similarities and related to each other. Along with the challenges, the researcher also discovered strategies done by all of the participants to resolve the problems, enrich the student’s vocabulary and improve the student’s writing English skills. Keywords: Teaching Vocabulary, EFL Student Teachers Challenges, COVID-19 Pandemic